Discourse in the making: the shifting meaning of the national flag in the context of Israel’s 2023 judicial overhaul - Silvia Adler; Ayelet Kohn (Humanities & Social Sciences Communications)
Abstract In the wave of protests that took place in Israel in 2023 in response to the government’s proposed judicial overhaul, a notable feature was the use of the Israeli flag as a prominent symbol. The protesters, identified mainly with the liberal center-left, reclaimed the flag, which until then had been largely associated with Israel’s political right, and used it to convey their commitment to the values of “Israeliness” which, they felt, were threatened by the judicial overhaul. In the context of the protest, the flag underwent mutations that superimposed various meanings on its basic value, expressing the diverse identities of the participating groups and reflecting the evolving agendas of associated social movements. The study seeks to explore the narratives and the symbolic messages conveyed by these mutations from the perspective of semiotic landscape theory and diverse approaches to multimodal discourse analysis, according to which meaning arises from inter-semiotic mechanisms allowing the expansion of meaning.